Health Policy Implementation for Promoting Healthy Islands - Muhammad Alwy Arifin; Nurul Syahriani Salahuddin (Yayasan Sinergi Kawula Muda, 2025)
The health of island communities is critical, yet often challenged by unique geographic and socio-economic factors. Effective health policy implementation plays a crucial role in promoting and maintaining healthy islands. This literature review examines the frameworks, challenges, and successful strategies for implementing health policies in island settings, drawing on case studies from various regions. The review highlights the importance of tailored policies that consider local contexts, community involvement, and intersectoral collaboration.